Determination of Hijri Calendar in Islamic History and Its Criteria in Southeast Asia - Kasim, A. Jusran; Abbas, Ahmad; Adhha, Nurul; Mutmainnah, Iin (Journal of Al-Tamaddun, 2024)
It is common for the beginning of Ramadhan and Shawwal to cause differences. In 2022, the imkān ar-ru’yah (visual moonsighting) Neo-MABIMS was introduced in Indonesia as an effort to unify the Islamic calendar. However, it is often compared to the hisab wujudul hilal (lunar calculation) method. This study aims to project the hilal (new moon) altitude and elongation angle after the implementation of Neo-MABIMS and compare the beginning of the month of Ramadhan and Shawwal between imkān ar-ru'yah and hisab wujudul hilal. A quantitative method was used to reveal differences between 2023 and 2031. Data was analysed using a comparative approach with the support of the Starry Night Pro Plus 6 and Accurate Hijri Calculator 2.2 applications. The results of this study show that a hilal altitude of 3° with an elongation angle greater than 6.4° was found in three periods for the beginning of Ramadhan (2023, 2029, 2030). Meanwhile, for the beginning of Shawwal, this was found in only two periods (2024 and 2031). In the comparison between imkān ar-ru’yah and hisab wujudul hilal, there will be differences marking the beginning of the month of Ramadhan in the years 2024, 2025, and 2030. Similarly, the onset of Shawwal will experience distinctions in 2023, 2026, and 2030. As a result, hisab (calculations) and ru’yah (sighting) adherents will differ on the day of celebration of Eid al Fitr to as many as three different dates.